Variability in anticoagulation duration and follow-up for deep venous thrombosis: a retrospective cohort study - Adam Darnley; Thomas Knight; Jecko Thachil (Clinical Medicine)
Introduction: Deep venous thrombosis (DVT) is frequently diagnosed in secondary care and increasingly managed in the ambulatory setting. Direct-acting oral anticoagulants (DOACs) are the preferred treatment to prevent recurrence because of their ease of use for the patients. Current guidelines recommend a minimum of 3 months of anticoagulation, followed by reassessment to determine the need for continued therapy.1 However, no structured follow-up pathway exists within our Trust. The absence of such a system may result in suboptimal treatment duration, increasing the risk of post-thrombotic syndrome, pulmonary embolism (PE), or prolonged anticoagulation with bleeding risks. This study evaluated follow-up practices, anticoagulation duration and clinical outcomes in patients diagnosed with DVT in ambulatory care. Materials and Methods: We conducted a retrospective cohort study using electronic patient records from two ambulatory care units in Manchester. Patients who underwent lower limb ultrasound for a suspected DVT during a period of 3 months were identified. Patients without a confirmed DVT diagnosis following ultrasound, those who died within 3 months of presentation and those already receiving DOAC therapy, or without accessible GP records, were excluded. Data were collected on the use of bleeding risk scores, anticoagulation duration documented at discharge, secondary care follow-up planned and subsequent thrombotic or bleeding complications. Results and Discussion: Of the 145 identified patients, 43 met inclusion criteria; 13 had a previous DVT and one had concurrent PE. Only one patient had a documented bleeding risk score at diagnosis. Anticoagulation duration varied: 16/43 were prescribed DOACs for 3 months, 10/43 for 6 months, 7/43 lifelong and 10/43 had no specified duration (Table 1). A discrepancy between duration on discharge prescriptions and GP records was identified in 21/43 (49%), mostly because of ongoing treatment beyond 6 months. Despite recommendations for reassessment, only 12/43 (28%) received secondary care follow-up, mainly in haematology (n=9), PE clinic (n=1), general medicine (n=1) or ambulatory care (n=1). Follow-up rates did not differ between patients with previous and first-time DVT (χ²(1)=1.03, p=0.310). All patients receiving secondary care follow-up had their anticoagulation extended beyond 3 months. However, 31/43 (72%) had no documented follow-up, and 4/31 developed recurrent DVT within 2 years. Of these, three had no transient risk factors, suggesting their recurrences may have been preventable. Conclusion: This study highlights inconsistencies in outpatient DVT management, particularly regarding anticoagulation duration and follow-up. Many patients did not receive the recommended 3-month reassessment, leading to variations in treatment duration and potentially preventable recurrences. Conversely, all patients reviewed in secondary care had their anticoagulation extended, with minimal bleeding complications. Given the complexity of long-term anticoagulation decisions, structured follow-up is essential to support shared decision-making and optimise outcomes. Our findings support the need for a standardised secondary care follow-up pathway to ensure appropriate anticoagulation management. Further research is needed to evaluate the safety and efficacy of such a framework.